Generation of a human induced pluripotent stem cell line (UALGi001-A) from a patient with Left-Ventricular Noncompaction Cardiomyopathy - Calado, Sofia (2021)
Left Ventricular Noncompaction Cardiomyopathy (LVNC) is characterized by excessive trabeculation of the left ventricle. To date, mutations in more than 40 genes have been associated with LVNC, however the exact mechanisms underlying the disease remain unknown. Here, we describe an induced pluripotent stem cell (iPSC) line (UALGi001-A) from a LVNC patient (LVNC-iPSC) that does not present mutations in the genes most commonly associated with the disease (van Waning et al., 2019). The LVNC-iPSC exhibited full pluripotency and differentiation potential, and retained a normal karyotype after reprogramming. This in vitro cellular model will be useful to study the molecular, genetic and functional aspects of LVNC.